Mannose-binding lectin suppresses macrophage proliferation through TGF-β1 signaling pathway in Nile tilapia - Mu, Liangliang; Yin, Xiaoxue; Bai, Hao; Li, Jiadong; Qiu, Li; Zeng, Qingliang; Fu, Shengli; Ye, Jianmin (Frontiers in Immunology, 2023)
Mannose-binding lectin (MBL) is a multifunctional pattern recognition molecule, which not only mediates the recognition of pathogenic microorganisms and their products, playing an important role in innate immune defense, but also participates in adaptive immune responses of mammalian. However, it’s related immune mechanism remains limited, especially the regulation of cell proliferation in early vertebrates. In this study, OnMBL was found to bind to kidney macrophages (MФ) from Nile tilapia (Oreochromis niloticus). Interestingly, OnMBL was able to reduce the proliferation of activated-MФ by regulating the cell cycle, arresting a large number of cells in the G0/G1 phase, and increasing the probability of apoptosis. More importantly, we found that the inhibition of cell proliferation by OnMBL was closely related to the evolutionarily conserved canonical transforming growth factor-beta 1 (TGF-β1) signaling pathway. Mechanistically, OnMBL could significantly increase the expression of TGF-β1, activate and regulate the downstream Smad-dependent pathway to reduce the MФ proliferation, thereby maintaining cellular homeostasis in the body’s internal environment. This study represents the first description regarding the regulatory mechanisms of the MBL on cell proliferation in teleost fish, which provides a novel perspective on the understanding of the multiple function and evolutionary origins of C-type lectins in the immune system.